Pengaruh Bauran Pemasaran Terhadap Niat Menjadi Mitra Perspektif Islam Pada BMT Beringharjo Cabang Madiun - Tyas, Mega Ayuning; Prasetyo, Ari (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
This study aims to analyze The Effect of Marketing Mix Towards Intention become Partner on Perspective of Islam at The Branch Office of BMT Beringharjo in Madiun. The tests carried out using multiple linear regression method, where the endogenous variable (Y) is a intention become partners and exogenous variables (X) is the marketing mix that is identified with product (X1), price (X2), place/distribution channel (X3), promotion (X4), people (X5), process (X6), physical evidence (X7), promise (X8), and patience (X9). In this study added two variables in the marketing mix of services in accordance with Islamic values that promise and patience.This study uses a quantitative approach. The characteristics of the population in this studi is a partner at The Branch Office of BMT Beringharjo in Madiun are actively engaged in transactions in 2014 and live in Madiun. Total sample of the respondents is 100 (one hundred). These samples were selected using nonprobability sampling with purposive sampling method with particular consideration.The results of this study indicate that simultaneous and partially, marketing mix variables consisting of product, price, place/distribution channel, promotion, people, process, physical evidence, promise, and patience shown the effect to intention become a partner on perspective of Islam at the branch office of BMT Beringharjo in Madiun. Variable place/distribution channel is the most dominant variable to the intention become partners on perspective of Islam at the branch office of BMT Beringharjo in Madiun.Suggestion for the branch office of BMT Beringharjo in Madiun should increase promotional activity to be more diverse so it can attract attention to prospective partners or partners who have joined, socialize product from BMT Beringharjo more clearly and detail, especially the difference with the product from conventional bank, and make a direct sales pitch way more exciting and creative by adding facilities and infrastructure in the promotion or by making a series of interesting activities and carried out in the crowd with direct sales activities.